2012
DOI: 10.4103/0972-5229.106511
|View full text |Cite
|
Sign up to set email alerts
|

Severe suicidal digoxin toxicity managed with resin hemoperfusion: A case report

Abstract: Owing to its wide and easy availability, digoxin has got a significant abuse potential and may be used for suicidal purposes. Digoxin-specific antibody (Fab) fragments have become the mainstay of therapy for severe digoxin toxicity and have significantly helped in reducing mortality. However, due to its high cost and limited availability alternative measures may need to be used to manage severe intoxications especially in countries like India, where Fab fragments are unavailable. Here, we present a case of a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scienti c evidence about the application of HA-280 and HA-230 cartridges in clinical settings (24,25). Previous study in which the e cacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could bene cially in uence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary in ammatory cytokines (12).…”
Section: Resultsmentioning
confidence: 99%
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scienti c evidence about the application of HA-280 and HA-230 cartridges in clinical settings (24,25). Previous study in which the e cacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could bene cially in uence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary in ammatory cytokines (12).…”
Section: Resultsmentioning
confidence: 99%
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scientific evidence about the application of HA-280 and HA-230 cartridges in clinical settings [ 26 , 27 ]. Previous study in which the efficacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could beneficially influence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary inflammatory cytokines [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used HA-280 and HA-230 cartridges because we did not have access to other types like cytosorb, Jafron HA-380, and HA-330 in our country. There is a limited scienti c evidence about the application of HA-280 and HA-230 cartridges in clinical settings (26,27). Previous study in which the e cacy of HA-330 resin-directed hemoperfusion has been assessed in acute respiratory distress syndrome, some considerable treatment outcomes including improved oxygenation, reduction in lung edema and histopathological signs of acute respiratory distress syndrome, and reduced circulating and alveolar cytokine levels have been resulted; and the authors concluded that this cartridge could bene cially in uence the course of acute respiratory distress syndrome by attenuating systemic and pulmonary in ammatory cytokines (12).…”
Section: Discussionmentioning
confidence: 99%